Temperature effects upon the bacteria of milk - Fryhofer, Charles Wesley (My University, 1905)
Introduciton: Bacteria are microscopic one-celled plants that reproduce by fission (cell division). Being of such minute size their great importance in the natural order things about us is not realized until we study their habits and. discover in a small measure their vast and unlimited extension over the whole earth. Bacteria grow and develop into the mature state as one single cell. This cell then divides, forming two offspring which grow and multiply in the same Way. Bacteria obtain their food by absorption through the protoplasmic tedium of which the cell is made up. Some are able to live only in air while others are always found in the absence of air. The first are termed: aerobic, and. the latter are the anaerobic germs. Some are able to live in extremely high temperature; others at very low temperatures. in nature we find that, being the simplest form of life, bacteria are adapted only to the conditions in which they are found, that is, different species are found living in different conditions as regards light, heat, air, foot. etc., and only under those conditions are they capable of the freest existence. Place these germs in different conditions and they will not increase. Place them in an altogether different medium and if all the necessary conditions above mentioned are supplied, they will continue to increase in that medium. This would-seem to indicate that bacteria, as found in nature, mild not be very numerous with such varying conditions. This, however, is not the case, for with every varying Condition we find species specially adapted to that condition. Bacteria reproduce with great rapidity in direct geometrical progression, providing all other conditions are equal. The average length of life from the time one cell divides until its offspring reproduce is but a few minutes to an hour. This May give some idea of the number of bacteria present about us.
Citation: Fryhofer, Charles Wesley. Temperature effects upon the bacteria of milk. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Effect on Varying Temperatures on Bacteria in Milk; Storrs Ivestigations; Temperature and Acidity; Theses